Factors impacting HIV testing among young sexually active women migrant workers in Vietnamese industrial zones - Toan Ha; Hui Shi; David Givens; Trang Nguyen; Nam Nguyen (BMC, 2023)
Abstract Background Young migrant workers living in low- and middle-income countries often experience barriers and inadequate access to HIV prevention and treatment services. This study examines the prevalence of HIV testing, associated factors, and reasons for obtaining and not obtaining HIV testing among young sexually active women migrant workers in an industrial zone in Hanoi, Vietnam. Methods A cross-sectional study was conducted among 512 sexually active young women migrant workers (aged 18 to 29) working in the Thang Long industrial zone in Hanoi, Vietnam. Data was collected via a face-to-face interview from January 2020 to June 2021. Multivariable logistic regression analysis was used to explore factors associated with ever-testing for HIV among sexually active participants. Results The study found a low level of HIV testing and high rates of unprotected sex. Among those who reported being sexually active, only 23.7% of participants (n = 126) reported having ever been tested for HIV. Among those who reported never having tested for HIV, 38.2% reported not using condoms during their most recent sexual encounter. Factors associated with engaging in HIV testing included being older (25-29 years), having greater knowledge about HIV, past use of sexual and reproductive health and HIV services, and familiarity with HIV testing locations. Conclusions Overall, a low level of HIV testing, high rates of unprotected sex, and low perceived risks regarding HIV among the study participants point to a need to implement targeted HIV interventions that can improve both safe sex practices and perceptions of and knowledge about risky sexual behaviors. Such interventions should use insights from this study to address factors facilitating HIV testing among industrial zones' women migrant workers.